Gynacantha anandmati, a new species of dragonfly (Odonata: Anisoptera: Aeshnidae) from Maharashtra, India - Sawant, Dattaprasad; Kambli, Amol (Zootaxa, 2023)
We erect Gynacantha anandmati sp. nov. based on one male and one female specimens collected from Thane district of Maharashtra. The new species is distinguished from its congeners by long, straight and nearly flat cerci, distinct ‘T-shaped mark’ on postfrons and vividly marked abdomen. We also provide updated key to identification of males of South Asian Gynacantha spp.